New Tool for Measuring Sustainable Development in Functional Urban Areas - Kociuba, Dagmara; Szafranek, Edyta (European Spatial Research and Policy, 2018)
The article discusses the practical aspect of implementation of the idea of sustainable development in the EU Cohesion Policy in the 2014-2020 programming period in Poland. The objective of the study is to determine the relations between the idea of sustainable development and instruments of its implementation, and the identification of the scope of influence of Cohesion Policy tools on sustainable development of functional urban areas (FUA). The paper presents the author’s set of sustainable development indicators (SDI) and relevant analyses of their implementation in the financial and spatial aspect in 26 FUAs. Detailed analyses covered one of the new instruments of territorial development, namely Integrated Territorial Investments (ITI). The paper provides evidence which proves that the dominant sphere in the financial and spatial support is the modernisation of transport and energy engineering infrastructure, with potentially multiple effects, as well as the development of a structurally diverse labour market. The least support is provided to the strengthening of integrated management. The tested approach is applicable in reference to other functional areas in the EU. It can contribute to the determination of the extent to which the implementation of the Cohesion Policy supports sustainable development of cities and their functional areas. The application of SDI contributed to the understanding of the process in reality.